(untitled) (e-Journal of Linguistics, 2024)
This article explores the field of feminist stylistics, a multidisciplinary approach to analyzing a poem titled “Being a Woman” through a feminist lens. By examining the stylistic choices and linguistic strategies in poetry, the article investigates how language can either reinforce or challenge prevailing gender norms and stereotypes. Focusing on three topics, feminism in stylistics, female sentences, and metaphor, we can construct a conclusion regarding the contents within the poem. We found that the theme of oppression and fighting against inequality is heavily prevalent within the poem. The author uses veiled words to hide their hidden antagonism against the male gender. In conclusion, this article emphasizes the critical role of feminist stylistics in redefining how we understand and interact with language in the context of gender. It offers valuable insights into the ways in which language can be both a tool of oppression and a vehicle for feminist empowerment.